2021
DOI: 10.2147/jaa.s316250
|View full text |Cite
|
Sign up to set email alerts
|

Muc5ac Production Inhibited by Decreased lncRNA H19 via PI3K/Akt/NF-kB in Asthma

Abstract: Introduction LncRNAs play important roles in multiple diseases including asthma, while there are a few reports on the role of lncRNA H19 about asthma. This study aimed to investigate the roles and mechanisms of lncRNA H19 in asthma. Methods We detected lncRNA H19 and Muc5ac mRNA by establishing a murine asthma model and an in vitro inflammation model. Regulatory roles of lncRNA H19 in asthma were explored by lncRNA H19 overexpression or knockdown in vitro. To study its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…[13][14][15]24 Besides, asthmatic mice showed that targeting EGFR by inhibiting EGFR phosphorylation can reduce smooth muscle and epithelial cell proliferation, reduce collagen deposition and goblet cell proliferation, and improve airway remodeling in asthma. 11,12,29 Multiple stimuli lead to hypersecretion of mucins via EGFR expression and activation, causing goblet cell metaplasia. 11,12 Consistently, our results showed that PTPRH elevated in serum and induced sputum of asthma patients and lung tissue of asthmatic model, and its expression negatively correlated with EGFR and MUC5AC, which suggests that PTPRH inhibits EGFR phosphorylation involved in epithelial damage/repair processes to relieve dysfunction of airway obstruction and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[13][14][15]24 Besides, asthmatic mice showed that targeting EGFR by inhibiting EGFR phosphorylation can reduce smooth muscle and epithelial cell proliferation, reduce collagen deposition and goblet cell proliferation, and improve airway remodeling in asthma. 11,12,29 Multiple stimuli lead to hypersecretion of mucins via EGFR expression and activation, causing goblet cell metaplasia. 11,12 Consistently, our results showed that PTPRH elevated in serum and induced sputum of asthma patients and lung tissue of asthmatic model, and its expression negatively correlated with EGFR and MUC5AC, which suggests that PTPRH inhibits EGFR phosphorylation involved in epithelial damage/repair processes to relieve dysfunction of airway obstruction and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,29 Multiple stimuli lead to hypersecretion of mucins via EGFR expression and activation, causing goblet cell metaplasia. 11,12 Consistently, our results showed that PTPRH elevated in serum and induced sputum of asthma patients and lung tissue of asthmatic model, and its expression negatively correlated with EGFR and MUC5AC, which suggests that PTPRH inhibits EGFR phosphorylation involved in epithelial damage/repair processes to relieve dysfunction of airway obstruction and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 Furthermore, several efforts have been dedicated to revealing the critical effects of the PI3K/AKT signaling pathway in airway remodeling, thereby promoting asthma progression. [17][18][19] In an instance, the authors demonstrated that inhibiting the abnormal upregulation of the PI3K/AKT signaling pathway could reduce the significant infiltration of inflammatory cells and airway remodeling, as well as improve lung function. 19 Nonetheless, it is uncertain regarding the participation of CST1 in the progression of asthma by the PI3K/AKT signaling pathway.…”
mentioning
confidence: 99%